?THE UPTAKE AND Loss OF ABSORBED DISSOLVED COPPER BY CMRlAS ANGllLLAlUS FINGERLINGS (Biological Sciences - PJSIR, 2000)
The uptake and loss of dissolved copper In media by the African: mud fish Clarias angullaris was studied! in water of 25mg 1-1hardness expressed as CaC03 of pH 6.8 at 27±2°C in a stanc test system. Th.euptake experiments involved exposure offish to 05, 0.75 and E_0mg Cu+z 1-1test so[utrom;; from whiclr the Irsn. absorbed! and!retained (l